Demand Response Design of Domestic Heat Pumps - Mohammed Jasim M. Al Essa (Designs, 2017)
This paper proposes an emergency-based demand response (DR) controller of domestic heat pump (DHP) units based on an estimated frequency of the UK electricity in 2035. The normal pattern of DHP demand is adjusted to maintain system frequency within its limit using a linear model of power and temperature inside low-carbon houses, while considering consumer comfort. Simulation results show that the proposed DR design of static/dynamic frequency-controlled DHPs will increase the amount of power reserve by 75% and the amount of electricity market by 70%, as compared to their values of the current frequency response by flexible loads.